Optical, dielectric and X-ray absorption properties of soda-based glass fabricated from Thai quartz sands doped with iron oxide - Pongkrapan S. (2014)
Soda-based glass samples were fabricated in a laboratory scale using quartz sands that was a by-product of feldspar floatation in Tak Province, northern Thailand, and 25-wt% commercial-grade Na2CO3 as the main compositions. Fe2O3 of 0.1 to 10.0 wt% concentrations was doped into the glass mixture. Well-mixed and dried powders were melted in a ceramic crucible for 6 h at 1250°C using an electric furnace. Transparent and bubble-free glass samples were obtained as results. It was found that Fe2O3 dopant turned the otherwise colorless glass to dark brown. Dielectric property and physical properties, such as, color, specific gravity, and refractive index of the glass samples were studied. The samples' dielectric constant, specific gravity, and refractive index increased with increasing Fe2O3 doping concentration. UV-VIS-NIR and synchrotron-based X-ray absorption spectra were measured and discussed. © (2011) Trans Tech Publications.